2015
DOI: 10.1111/ced.12698
|View full text |Cite
|
Sign up to set email alerts
|

Does dermatoneuro syndrome have a viral aetiology?

Abstract: Scleromyxoedema is a rare disease characterized by a generalized papular and sclerodermoid cutaneous eruption. It is associated with fibroblast proliferation and mucin deposition in the dermis. Most patients have a monoclonal gammopathy, defined by the presence of IgG. Treatment of scleromyxoedema is challenging, but there is mounting evidence to support the use of intravenous immunoglobulin (IVIg). Individual reports of systemic complications have been described. Dermatoneuro syndrome (DNS) is a rare but some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
5
0
3
Order By: Relevance
“…One previous case report has reported a possible link between influenza A and DNS development in patients with scleromyxedema [1], and two more patients are reported here. Particularly in our first patient this is unlikely to be an influenza encephalopathy case, considering the normal magnetic resonance imaging findings, negative CSF influenza polymerase chain reaction, and clinical improvement after IVIG.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…One previous case report has reported a possible link between influenza A and DNS development in patients with scleromyxedema [1], and two more patients are reported here. Particularly in our first patient this is unlikely to be an influenza encephalopathy case, considering the normal magnetic resonance imaging findings, negative CSF influenza polymerase chain reaction, and clinical improvement after IVIG.…”
Section: Discussionsupporting
confidence: 56%
“…DNS aetiology is unclear [1]. Here two patients are described who developed DNS and tested positive for influenza A virus.…”
Section: E T T E R S T O T H E E D I T O R Two Patients With Dermaton...mentioning
confidence: 97%
See 1 more Smart Citation
“…The pathogenesis of DNS remains uncertain; however, reports speculate that elevated levels of vasoactive cytokines (eg, interleukin 6) during viral infection may contribute by compromising the blood-brain-barrier. 5,6 Enhanced blood-brain-barrier permeability in the setting of monoclonal gammopathy may elevate IgG levels in the brain microvasculature, causing hyperviscosity, sludging, and neurologic abnormalities. [7][8][9] Available literature indicates that reported cases of DNS are frequently preceded by a flu-like prodrome 3,4,[9][10][11][12][13][14][15][16][17][18] or other suspected upper respiratory tract infection.…”
Section: Introductionmentioning
confidence: 99%
“…8,19 Notably, 2 case studies identified influenza A infection in association with DNS. 6,10 Here, we describe a patient with SMX complicated by 2 episodes of DNS, each associated with different RNA virus infections: Influenza A or SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%